High-Strain Deformation and Spallation Strength of 09CrNi2MoCu Steel Obtained by Direct Laser Deposition - Olga Klimova-Korsmik; Gleb Turichin; Ruslan Mendagaliyev; Sergey Razorenov; Gennady Garkushin; Andrey Savinykh; Rudolf Korsmik (Metals, 2021)
In this work, the critical fracture stresses during spalling of high-strength steel 09CrNi2MoCu samples obtained by direct laser deposition (DLD) were measured under shock compression of up to ~5.5 GPa. The microstructure and mechanical properties of DLD steel samples in the initial state and after heat treatment were studied and compared to traditional hot rolled one. The microstructural features of steel before and after heat treatment were revealed. The heat treatment modes of the deposit specimens on their strength properties under both static and dynamic loads have been investigated. The spall strength of the deposited specimens is somewhat lower than the strength of steel specimens after hot rolling regardless of their heat treatment. The minimum elastic limit of elasticity is exhibited by the deposit specimens. After heat treatment of the deposit samples, the elastic limit increases and approximately doubles. Subsequent heat treatment in the form of hardening and tempering allows obtaining strength properties under Hugoniot loads in traditional hot-rolled products.